POWERS OF DISTRICT STATE ADMINISTRATIONS IN THE FIELD OF LAND RELATIONS MANAGEMENT: ANALYSIS OF LEGISLATIONAND PRACTICE - Mamonova, Valentyna; Kojurina, Vira (Pressing Problems of Public Administration, 2021)
The article provides a scientific analysis of the regulation of the powers of district state administrations in the field of land management. It was determined that the normative securing of the functions of the district authorities in land management, as well as the regulation of environmental safety requires unification, since in the basic laws the norms differ in content and formulation. These powers need to be reflected in the structure of the district state administration, in accordance with the basic law of administration (the structure of the public authority must correspond to the functions). In order to study the practice, the structure of 40 district administrations of different regions of Ukraine was analyzed; it was found that the actual structure does not correspond to the functional load, which is enshrined in the legislation. It is such inconsistencies that make it impossible to move to the second stage of decentralization, which is already taking place at the legislative level. A scientific analysis of the results of the survey of officials of district and local authorities was carried out. The survey was conducted in the districts that were among the first to complete the process of uniting territorial communities. The topic of the survey was the distribution of powers and responsibilities in various areas, in particular in the field of land relations and environmental issues. It has been established that there is a general tendency to the blurring of the district level of power, since the bulk of powers was given to local governments. A number of functions (control) have been considered expedient to perform together by employees of both structures .The problems that may arise in the cooperation of DSA and local governments in the outlined area have been considered. Approaches to the distribution of powers depending on the stage of land decentralization implementation and the role of DSA in each of the two proposed administration models have been analyzed